On the Existence of Periodic Solutions of a System of Two Differential Equations with Pulse Influence - Moroz, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate the problem of the existence of periodic solutions of a system of two linear differential equations with pulse influence on a plane in the case where a stable knot or a stable focus is a singular point of this system.